Do Improvements in Therapeutic Game-Based Skills Transfer to Real Life Improvements in Children's Emotion-Regulation Abilities and Mental Health? A Pilot Study That Offers Preliminary Validity of the REThink In-game Performance Scoring - David, Oana A.; Magurean, Silvia; Tomoiagă, Cristina (Frontiers in Psychiatry, 2022)
Therapeutic or serious games are considered innovative ways of delivering psychological interventions especially suited for children and adolescents, which can have a positive impact on mental health, while also being fun and easily accessible online. While most serious games for children and adolescents address specific issues, such as anxiety or depression, preventive measures received less attention. REThink is an online therapeutic game designed as a stand-alone prevention tool, aiming to increase resilience in healthy children and adolescents in a Rational Emotive Behavioral Therapy framework (David, Cardos, & Matu, 2019). The aim of this pilot study was to investigate the validity of in-game performance measurements or scores as indicators of the game effectiveness in building real life emotion-regulation abilities. We analyzed how scores of different game levels (addressing different skills) are associated with improvements in mental health and emotion regulation abilities. Our preliminary results suggest that in-game performance at some levels (scores) consistently reflect improvements in psychological functioning, while in-game performance at other levels are less associated with changes in real life self-reported psychological functioning. These results offer important information about which levels can be used as preliminary indicators of psychological improvements, and which levels need to be revised in terms of task or scoring. Overall, results of our study offer preliminary validation of REThink’s game scoring system, while also suggesting the elements to be refined.